Komparasi Kadar Daya Dukung Tanah Berbutir Halus Berdasarkan Uji CBR Menggunakan Alat Tekan Modifikasi dan Modified Proctor - Damayanti, Amelia Nurul; Adha, Idharmahadi; Zakaria, Ahmad (Universitas Lampung, 2020)
The importance of soil as construction material needs to be considered carefully. With various soil conditions, a physical test is required to discover the characteristics of the soil and California Bearing Ratio (CBR) test in a laboratory to determine the bearing capacity of the basic land (subgrade). This research was conducted to assess the suitability of the CBR test value with two different compaction tools. The results of this study showed that the soils were classified into A-6 clay soil type. On the modified proctor compaction test, the maximum weight volume (γdmaks) was 1,70 gr/cm3, while the compaction with modified press tool obtained 1,75 gr/cm3. Based on the results of the values obtained from CBR standard test is 11,5% and 1,32% for the soaked sample .While the CBR value without immersion with modified press tool are 7,7% for 3 MPa, 16,2% for 6 MPa, 19,5% for 9 MPa, 20,5% for 12 Mpa. For the soaked samples are 1,53% for 3 Mpa, 2,7% for 6 Mpa, 3,56% for 9 Mpa, and 4,33% for 12 Mpa. In conclusion, the CBR value escalation is higher when using the modified pressure tool compared with the CBR standard method.